PENGARUH TEKANAN ANGGARAN WAKTU DAN RESIKO KESALAHAN TERHADAP PENURUNAN KUALITAS AUDIT - Asna Manullang (STIE Pelita Nusantara Semarang, 2010)
This paper investigates critical issues on ethical behavior, specifically the role of an individual’s perception of situation-specific issues on decision making process in moral situation related to some accounting situation. A person who perceived moral problem does not always make moral-decision in practice because he/she tend to ignore moral issues when be faced with technical-characteristic situation.This investigation prove the difference of Moral Intensity as well as Moral Sensitivity, Moral Judgment, and Moral Intention were not always create a person’s moral-decision in some accounting moral problem situation.